2022
DOI: 10.3389/frans.2022.1039606
|View full text |Cite
|
Sign up to set email alerts
|

A quantification method for trace level of oxytocin in food matrices using LC-MS/MS

Abstract: Backgrounds: Oxytocin is nowadays used to increase the agricultural products besides its use during the milking of cattle leading to the contamination of agricultural produce and milk with oxytocin. Monitoring of accurate oxytocin contaminations from foodstuffs is sometimes required to maintain the quality standard. The commonly used oxytocin assays in this study were interfered with by the food matrix. There is a need to develop an accurate and confirmed method for monitoring oxytocin contaminations in foodst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous studies have also reported similar observations, highlighting the potential of hydrophilic and rigid spacers to improve assay sensitivity and specificity. It has also been previously reported that the spacer length does not bear any correlation with the assay sensitivity in ELISA ( 1 5 , 11 , 19 , 20 ) as it does have an effect in some other immunoassays and auxiliary binding systems ( 9 11 , 20 ). The use of a hydrophilic and rigid spacer possibly helped in projecting the hapten away from the enzyme, leading to an enhanced antibody binding signal and improved sensitivity of the assay ( 9 11 , 14 , 20 ).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous studies have also reported similar observations, highlighting the potential of hydrophilic and rigid spacers to improve assay sensitivity and specificity. It has also been previously reported that the spacer length does not bear any correlation with the assay sensitivity in ELISA ( 1 5 , 11 , 19 , 20 ) as it does have an effect in some other immunoassays and auxiliary binding systems ( 9 11 , 20 ). The use of a hydrophilic and rigid spacer possibly helped in projecting the hapten away from the enzyme, leading to an enhanced antibody binding signal and improved sensitivity of the assay ( 9 11 , 14 , 20 ).…”
Section: Discussionmentioning
confidence: 95%
“…The concentration was plotted on the X-axis (log scale) and the A/A0x100 on the Y-axis. The values of the unknown samples were calculated by an in-house–developed personal computer program written in QBASIC language using the logit–log linear regression method according to the method described elsewhere ( 5 ). The affinity constant of the PSL antibody for PSL was estimated by a Scatchard plot according to the method described elsewhere ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations